An anthology of outstanding achievements in science and technology. Part 21: Artificial intelligence and robotics - M.I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2014)
A brief essay on the history of invention of various-application robots and development of state-of-the-art robotics is given.